Retronasal olfactory function in patients with smell loss but subjectively normal flavor perception - Liu, David Tianxiang; Besser, Gerold; Renner, Bertold; Seyferth, Stefan; Hummel, Thomas; Mueller, Christian Albert (Laryngoscope, 2019)
Objectives The human sense of smell constitutes the main part of flavor perception. Typically, patients with loss of olfactory function complain of diminished perception during eating and drinking. However, some patients with smell loss still report normal enjoyment of foods. The aim of the present study was to compare orthonasal and retronasal olfactory function in patients with non-sinonasal smell loss and subjectively normal flavor perception. Methods Nineteen patients (mean age [range] 52.0 [8-83 years]) with self-reported olfactory impairment but subjective normal flavor perception were included. Olfactory performance was assessed using the Sniffin' Sticks (TDI) for orthonasal and the Candy Smell Test (CST) for retronasal function. Visual analogue scales were used for self-assessment of odor (SOP), taste (STP), and flavor perception (SFP), ranging from 0 (no perception) to 10 (excellent perception). Results Mean (SD) SFP was 8.0 (1.8). Mean (SD) orthonasal TDI-score of all patients was 14.4 (5.3, range 6-25.3) with 11 patients classified as anosmic and eight as hyposmic. Mean/SD retronasal CST-score was 8.8 (2.7, range 3-13) within the range of anosmia/hyposmia. No correlation was found between SFP and the CST (P = .62). Conclusion The present results showed that despite claiming normal flavor perception, our patients were ortho- and retronasally dysosmic using standard tests for olfactory function. Although other explanations could be possible, we suggest that this subjective flavor perception might be due to unconscious memory recall from previously experienced cross-modal sensory interactions. Level of Evidence 4 Laryngoscope, 2019
CRIS-Team WoS Importer:2019-09-20